2022
DOI: 10.1186/s12966-022-01354-5
|View full text |Cite
|
Sign up to set email alerts
|

Is level of implementation linked with intervention outcomes? Process evaluation of the TransformUs intervention to increase children’s physical activity and reduce sedentary behaviour

Abstract: Background TransformUs was a four-arm school-based intervention to increase physical activity and reduce sedentary behaviour among primary school children. Pedagogical and environmental strategies targeted the classroom, school grounds and family setting. The aims of this study were to evaluate program fidelity, dose, appropriateness, satisfaction and sustainability, and associations between implementation level and outcomes among the three intervention arms. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Nonetheless, the effects of adaptation on intervention effects can be mixed. For example, in school-based physical activity research, level of adaptation (fidelity) may not be associated with program efficacy [ 56 ] or lead to reduced effects [ 57 ]. This highlights the importance of enabling and integrating ways for intervention components to be adapted and monitoring the associated outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the effects of adaptation on intervention effects can be mixed. For example, in school-based physical activity research, level of adaptation (fidelity) may not be associated with program efficacy [ 56 ] or lead to reduced effects [ 57 ]. This highlights the importance of enabling and integrating ways for intervention components to be adapted and monitoring the associated outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Australia, one contributing factor to the Victorian State Governments’ decision to scale the TransformUs initiative was that it coincided with the launch of a state-wide physical activity target [ 56 ]. In Canada, the scaling of Action Schools!…”
Section: Resultsmentioning
confidence: 99%
“…A recent process evaluation of the trial found that at 18 months, responding teachers (50% response rate) delivered 70% of the nine key learning messages, and almost one in five teachers provided children with active homework once a week. 49 One-third of the teachers delivered an active lesson and 56% delivered an active break every day, and almost all teachers provided access to the physical activity/sports equipment during recess and lunch breaks as well as during class lessons. The use of active pedagogy increased over time as did the use of line markings in the playground for lesson delivery.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the programme strategies 31 and programme logic model has been published elsewhere. 20 Adaptations to the TransformUs programme for scale-up are described later in the Methods section, and online supplemental file 1 presents the evolution of TransformUs since the original RCT (2009) to date.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 20 Existing teaching practices, children’s enjoyment and teacher awareness of programme values and benefits were the main facilitators of delivery and sustainability. 20 Following the success of TransformUs , and exploration of adaptations for scaling (described in the Methods section), the Victorian Department of Education committed to partnering with the research team to support the dissemination and implementation of the programme to all primary (elementary) schools in Victoria, Australia. Given the small number of school-based interventions that are studied at scale 27 and that use implementation theories to guide this process, 28 29 scaling up of TransformUs presented a unique opportunity to investigate real-world implementation at scale.…”
Section: Introductionmentioning
confidence: 99%